Outcome of Peritoneal Dialysis in Children : Experience in a Tertiary Level Hospital in Chittagong, Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Objective: The objective of the study is to see the outcome of peritoneal dialysis in child age group ranging from 6 months to 15 yearsadmitted in ChattagramMaa- Shishu-O-General Hospital ICU setup. Methods: Patients were selected randomly who admitted with the indication of renal replacement therapy.Intermittent peritoneal dialysis was done in 10 patients from February 2012 to January 2013. Results: Out of ten patients eight survived and two died due to complication.The success rate is 80%.Among the survivors four made complete recovery with no complication and another fourwere sent to paediatric surgery for treatment of obstructive uropathy, the primary cause of the renal failure. Conclusion: The data presented indicate that peritoneal dialysis is an effective type of dialysis, that it is safe, that it can be accomplished with a minimum of equipment and that a trained team is essential for its efficient use. It is the preferable practical procedure currently available by which dialysis of an anuric infant or small child can be accomplished. Chattagram Maa-O-Shishu Hospital Medical College Journal Volume 12, Issue 3, September 2013: 34-36